ANALISIS KEBUTUHAN KEBUGARAN JASMANI UNTUK KESIAPAN BEKERJA PADA SISWA SMK TARUNA KARYA MANDIRI - Daffa Rafid Setiawan; Setio Nugroho; Rekha Ratri Julianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study comprehensively analyzes the physical fitness requirements for work readiness among students at SMK Taruna Karya Mandiri. Work readiness is a critical factor for vocational high school graduates, and physical fitness plays a significant role in enhancing work performance, productivity, and reducing the risk of occupational injuries. Employing a descriptive quantitative research method with a survey approach, supplemented by in-depth interviews, the study gathered data from physical fitness tests administered to students and qualitative insights from key stakeholders including sports teachers, curriculum teachers, industrial relations teachers, and corporate HR representatives. Quantitative results indicate that the distribution of physical fitness levels among students is as follows: 2.00% in "Very Good" category, 21.00% in "Good", 53.33% in "Sufficient", and 23.67% in "Less". This highlights that while a foundational level is met by most, significant improvement is needed, particularly for those in the "Less" category. Qualitative findings from interviews consistently underscore that optimal physical condition is paramount for sustained performance in both academic and professional environments. It is perceived as a primary determinant of readiness and competitiveness in the labor market. This research aims to provide a robust foundation for developing more tailored curricula and training programs that enhance students' physical fitness, thereby bolstering their overall work readiness and alignment with industrial demands